Identifying joint impacts of sun radiation, temperature, humidity, and rain duration on triggering mental disorders using a high-resolution weather monitoring system - Deng, Xinlei; Brotzge, Jerald; Tracy, Melissa; Chang, Howard H.; Romeiko, Xiaobo; Zhang, Wangjian; Ryan, Ian; Yu, Fangqun; Qu, Yanji; Luo, Gan; Lin, Shao (Environment international, 2022)
[Display omitted] •High solar radiation + relative humidity + temperature posed the highest MD risk.•MD effects in September and October > summer.•Minorities, males, older adults, and uninsured patients were more vulnerable. Mental disorders (MDs) are behavioral or mental patterns that cause significant distress or impairment of personal functioning. Previously, temperature has been linked to MDs, but most studies suffered from exposure misclassification due to limited monitoring sites. We aimed to assess whether multiple meteorological factors could jointly trigger MD-related emergency department (ED) visits in warm season, using a highly dense weather monitoring system. We conducted a time-stratified, case-crossover study. MDs-related ED visits (primary diagnosis) from May-October 2017–2018 were obtained from New York State (NYS) discharge database. We obtained solar radiation (SR), relative humidity (RH), temperature, heat index (HI), and rainfall from Mesonet, a real-time monitoring system spaced about 17 miles (126 stations) across NYS. We used conditional logistic regression to assess the weather-MD associations. For each interquartile range (IQR) increase, both SR (excess risk (ER): 4.9%, 95% CI: 3.2–6.7%) and RH (ER: 4.0%, 95% CI: 2.6–5.4%) showed the largest risk for MD-related ED visits at lag 0–9 days. While temperature presented a short-term risk (highest ER at lag 0–2 days: 3.7%, 95% CI: 2.5–4.9%), HI increased risk over a two-week period (ER range: 3.7–4.5%), and rainfall hours showed an inverse association with MDs (ER: −0.5%, 95% CI: 0.9-(-0.1)%). Additionally, we observed stronger association of SR, RH, temperature, and HI in September and October. Combination of high SR, RH, and temperature displayed the largest increase in MDs (ER: 7.49%, 95% CI: 3.95–11.15%). The weather-MD association was stronger for psychoactive substance usage, mood disorders, adult behavior disorders, males, Hispanics, African Americans, individuals aged 46–65, or Medicare patients. Hot and humid weather, especially the joint effect of high sun radiation, temperature and relative humidity showed the highest risk of MD diseases. We found stronger weather-MD associations in summer transitional months, males, and minority groups. These findings also need further confirmation.